PIV-MyoMonitor: an accessible particle image velocimetry-based software tool for advanced contractility assessment of cardiac organoids - Lee, Hoyeon; Kim, Boyoung; Yun, Jiyue; Bae, Jinseung; Park, Sungsu; Jeon, Junseok; Jang, Hye Ryoun; Lee, Jaecheol; Lee, Soah (Frontiers in Bioengineering and Biotechnology, 2024)
We developed an open-source particle image velocimetry-based software program for advanced contractility assessment of various cardiac models. PIV-MyoMonitor enables comprehensive quantitative assessment and advanced visualization of the contractile function across cardiac models, from single cells to 2D monolayers to 3D engineered heart tissues to 3D cardiac organoids. This novel tool can help investigate the biomechanics of cells and tissues for studying cardiovascular physiology and pathology.